Evacetrapib and cardiovascular outcomes: reasons for lack of efficacy - Filippatos, Theodosios D.; Elisaf, Moses S. (Journal of Thoracic Disease, 2017)
Cholesteryl ester transfer protein (CETP) inhibitors are a drug class targeting the enzyme CETP (1). The first CETP inhibitor, torcetrapib, was discontinued because of increased cardiovascular events that were attributed to off-target adverse effects (increased aldosterone and blood pressure) (2).